2000
DOI: 10.1046/j.1472-765x.2000.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two assays, MSRV and RV, for the isolation of Salmonella spp. from wastewater samples and broiler chickens

Abstract: A . Z D R A G A S , P . T S A K O S A N D P . M A V R O G E N I . 2000.The Rappaport Vassiliadis (RV) and the Modi®ed Semi-solid Rappaport Vassiliadis (MSRV) methods were evaluated in 130 municipal wastewater samples and 30¯ocks of broilers. Analysis of the results showed that 71 Salmonella serotypes were isolated in wastewater samples. The positivity of the MSRV method was 33% and of the RV method, 45%. The sensitivity was 95% and 83% with the MSRV and RV, respectively. The concordance between the two methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…It is clear that in our study, based on more than 3000 broiler faecal and environmental samples, the highest number of positives was obtained by motility enrichment. This is in agreement with Voogt et al [24] who found a significantly higher performance of Diasalm and MSRV compared with RV for 892 broiler faecal samples, and with Zdragas et al [25] who found a higher sensitivity of MSRV compared with RV for 180 broiler internal organ and intestinal samples. Although the combination of these two semisolid media yielded a detection rate of 98n8%, it is debatable if this can be generalized.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is clear that in our study, based on more than 3000 broiler faecal and environmental samples, the highest number of positives was obtained by motility enrichment. This is in agreement with Voogt et al [24] who found a significantly higher performance of Diasalm and MSRV compared with RV for 892 broiler faecal samples, and with Zdragas et al [25] who found a higher sensitivity of MSRV compared with RV for 180 broiler internal organ and intestinal samples. Although the combination of these two semisolid media yielded a detection rate of 98n8%, it is debatable if this can be generalized.…”
Section: Discussionsupporting
confidence: 91%
“…S. Panama) or strains which form part of about 0n1% of the clinical human isolates [28]. It has also been reported that MSRV partially inhibits S. Typhimurium [25]. Also, the highly selective environment of the semisolid media (supplemented with 20 mg\l or 10 mg\l novobiocin in MSRV and Diasalm, respectively) could suppress some injured salmonella strains [27].…”
Section: Discussionmentioning
confidence: 99%
“…Salmonellosis is a major economic problem for the food industry and a public health hazard in many countries (RUMEU et al 1997, WAN et al 2000, ZDRAGAS et al 2000. Salmonella enterica, the causative agents of Salmonellosis, represent one of the most common reasons of outbreaks of food poisoning worldwide, estimated 1.4 million annual cases in the United States (LACEY 1993, DAUM et al 2002.…”
mentioning
confidence: 99%
“…from municipal wastewater samples and specimens of broilers of slaughtering age (Zdragas et al, 2000). from municipal wastewater samples and specimens of broilers of slaughtering age (Zdragas et al, 2000).…”
Section: Modified Semisolid Rappaport-vassiliadis Mediummentioning
confidence: 99%